Early and Mid-Term Implications of the COVID-19 Pandemic on the Physical, Behavioral and Mental Health of Healthcare Professionals: The CoPE-HCP Study Protocol - Khanji, Mohammed Y.; Maniero, Carmela; NG, Sher; Siddiqui, Imrana; Gupta, Jaya; Crosby, Louise; Antoniou, Sotiris; Khan, Rehan; Kapil, Vikas; Gupta, Ajay (Frontiers in Psychology, 2021)
Introduction The COVID-19 pandemic has led to unprecedented strain to healthcare systems worldwide and posed unique challenges to the healthcare professionals (HCPs) and the general public. Objectives The aim of this study is to evaluate the impact of COVID-19 on the mental health, behavioural, and physical wellbeing of HCPs in the early and mid-term periods of the pandemic in comparison to non-HCPs. Thus, facilitating and guiding optimum planning and delivery of support to HCPs. Methods and analysis An observational cross-sectional survey and case-control cohort study aiming to enrol over 1050 participants (minimum, 800 HCPs and 250 controls). Study questionnaires will be completed at baseline and after 6-weeks and 4-months. Recruitment initiated July 2020. The study was designed in London, UK, but open to participants worldwide. Baseline: Questionnaires comprising of validated self-administered screening tools for depression, anxiety, sleep-related issues, wellbeing and burnout. The questionnaires also explore changes in behaviour and physical wellbeing of the participants. In addition, associations of these mental health and behavioural factors with work-related factors and support will be explored. Six-weeks and 4-months follow-up: Follow-up questionnaires will assess change in symptoms of anxiety and depression, sleep disorders, use of alcohol and other substances, behavioural or interpersonal relationship changes. Physical wellbeing will be assessed through the presence of suspected or confirmed COVID-19 infection and absence from work. We will also evaluate the impact of variable provision of personal protection equipment (supply and training), extended working hours, and concern for the wellbeing of family members, anxiety levels and evidence of burnout. Statistical considerations The study has 80% power to detect a 10% difference of combined depression and/or anxiety symptoms between the groups using two-sided type 1 error at 0.05 at baseline. Assuming that only 50% of these HCPs agree to be a part of a cohort survey, we will have 80% power to detect around 12% difference in the two groups in reported physical symptoms (20% vs. 32.3%), or prevalence of depression and/or anxiety at the end of the study. Ethics The study was approved by the Cambridge East, Research Ethics Committee (20/EE/0166). Trial registration number ClinicalTrials.gov NCT04433260